Early life stages of an arctic keystone species (Boreogadus saida) show high sensitivity to a water-soluble fraction of crude oil. (November 2016) - Nahrgang, Jasmine; Dubourg, Paul; Frantzen, Marianne; Storch, Daniela; Dahlke, Flemming; Meador, James P.
Abstract: Increasing anthropogenic activities in the Arctic represent an enhanced threat for oil pollution in a marine environment that is already at risk from climate warming. In particular, this applies to species with free-living pelagic larvae that aggregate in surface waters and under the sea ice where hydrocarbons are likely to remain for extended periods of time due to low temperatures. We exposed the positively buoyant eggs of polar cod ( Boreogadus saida ), an arctic keystone species, to realistic concentrations of a crude oil water-soluble fraction (WSF), mimicking exposure of eggs aggregating under the ice to oil WSF leaking from brine channels following encapsulation in ice. Total hydrocarbon and polycyclic aromatic hydrocarbon levels were in the ng/L range, with most exposure concentrations below the limits of detection throughout the experiment for all treatments. The proportion of viable, free-swimming larvae decreased significantly with dose and showed increases in the incidence and severity of spine curvature, yolk sac alterations and a reduction in spine length. These effects are expected to compromise the motility, feeding capacity, and predator avoidance during critical early life stages for this important species. Our results imply that the viability and fitness of polar cod early life stages is significantly reduced when exposed to extremely low and environmentally realistic levels of aqueous hydrocarbons, which may have important implications for arctic food web dynamics and ecosystem functioning. Graphical abstract: Highlights: First ecotoxicological study on polar cod early life stages. Exposure to crude oil water-soluble fraction with sum26PAHs below 2 μg/L. The proportion of viable, free-swimming larvae decreased significantly with dose. The incidence and severity of developmental abnormalities increased with dose. Spine length was reduced with dose. Abstract : Levels of crude oil water-soluble fraction with Ʃ26PAHs in the ng/L range affect significantly the viability of polar cod larvae.